Behavioral deformation model for virtual animal dissection - Abdullah, Lili Nurliyana; Md Ali, Nor Azura (IEEE, 2012)
In this paper, we proposed a new method for computer dissection on animal as we use a set of techniques from behavioral deformation model. The reconstruction task was break down into 2 main steps: computation of the collision detection and the modeling of the external shape of neck and the four internal arborescence. The computer simulation tool was developed to manipulate the model and to define surgical resection planes according to internal animals. The first step of dissection simulation was implementing, embedding the model with the behavioral deformation computation. In this paper, we describe how to produce a realistic 3D model of the cow with collision detection for animal and slaughtering training. We address the problems of physical modeling and force feedback and how they relate to 3D representation and behavioral interaction. This research will also to make recommendations on the technologies required to create a virtual environment for the simulation of an animal dissection procedure incorporating haptic feedback. Our initial result is straightforward but is in significant improvements in the efficient physically based simulation of highly detailed parts.